EFFECT OF INPUT USE EFFICIENCY OF RICE PRODUCTION AMONG BENEFICIARIES AND NON-BENEFICIARIES OF ANCHOR BORROWERS’ PROGRAMME IN KADUNA STATE NIGERIA - Sunday, I.N.; Yusuf, U.O.; Isah, A.S.; Danladi E.B.; Hussaini, A.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study investigates the effect of input use efficiency of rice production among beneficiaries and non- beneficiaries of Central Bank of Nigeria Anchor borrowers’ programme (ABP) in Kaduna State. Multistage sampling procedure include the purposive selection of the three Local Government Areas (LGAs): Kaduna South, Chukun, and Igabi where rice production is prominence in the state; two communities was randomly selected from each of the three selected LGAs to give a total of six selected communities. Finally, 110 each of upland rice farmers who were RIFAN and NON-RIFAN member beneficiaries of ABP were randomly selected from the targeted communities. Descriptive statistics and stochastic frontier model were used in analyzing data collected for the study area. The findings revealed that there were no significant differences between the socio-economic characteristics of both categories of farmers. Findings revealed that beneficiaries of ABP technical efficiency scores ranged from 0.71 and 1.00 with an average of 0.91. The scores for their allocative and economic efficiency ranged from 0.62 - 0.99 and 0.44 - 0.99 with an average of 0.93 and 0.85, respectively. While for the non-beneficiary rice farmer of the ABP, technical efficiency scores ranged from 0.52 and 0.89 with an average of 0.81. The scores for their allocative and economic efficiency ranged from 0.57 – 0.97 and 0.39 - 0.72 with an average of 0.76 and 0.65, respectively. From the finding it can be concluded that the mean technical, allocative and economic efficiencies for of both beneficiaries and non- beneficiaries were below the frontier of one. The three most critical constraints for beneficiary and non-beneficiary were lack and poor extension services, high cost of inputs, and untimeliness of inputs distribution for beneficiary, and insufficient planting seeds for non-beneficiary. It is therefore recommended that government at the federal, state and local government levels should provide adequate extension services to rice farmers and also rice farmers should be encouraged by the extension agents to join and participate in cooperative societies so that Government and NGOs can easily reach out to them through this medium.